Da arquivística técnica à arquivística científica : a mudança de paradigma - Ribeiro, Fernanda (2002)
The dominant paradigm in Archivistics, called historical-tech-nicist, which arose after the French Revolution and evolved during the XIX and the XX centuries, is put in confrontation with a new one - the scientific-informational - which emerges into the context of the Information Society. In the light of this new perspective, Archivistics is understood as an applied branch of Information Science, with a clear object of study - the archives as an information system - and a scien-tific method of research, that operates by quadripolar dynamics and includes quantitative and qualitative approaches.